Corelation of Mesiodistal Width of Upper Anterior Teeth with Inner Canthal Distance in Population of Hyderabad Region (Medical Forum Monthly, 2020)
Objective: To determine the correlation of mesiodistal width of upper anterior teeth with inner canthal distance in population of Hyderabad region.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the Department of Prosthodontics, Liaquat University of Medical & Health Sciences (LUMHS) Jamshoro from June 2018 to January 2019.Materials and Methods: Total 122 subjects were included with convenient sampling technique. The data was collected by measuring the inner-canthal distance (ICD), with Vernier caliper by placing against the forehead and lowered towards the eyes. The external arms of the Vernier caliper were adjusted so that they were in gentle contact with medial angles of the palpebral fissures of the eyes. The distance between these two anatomical landmarks were recorded as the ICD represented in millimeters.Three readings of ICD were done to ensure precision and the mean value was recorded. The mesiodistal widths (MDW) of each maxillary central incisor, lateral incisor and canine were recorded intra-orally. The combined width of upper anterior (CWUA) teeth was calculated by summing up the widths of central incisors, lateral incisors and canine of both contralateral sides. Then the combined widths of maxillary anteriors were co-related with the ICD. The readings were recorded in proforma. The Data was analyzed by SPSS version 16.Results: The mean age was 28.16±5.508. The males were 61% and female were 39%. Comparison of mean score of ICD in male was 29.38±2.44 and in female was 28.97±2.01 which is statistically not significant. Comparison of mean score of CWUA teeth in male was 32.68±2.69 and in female was 32.02±2.31; statistically not significant. Pearson correlation of ICD with CWUA was positive and statistically significant.Conclusion: The results of the present study suggest that ICD may be a reliable predictor to determine the MDW of upper anterior teeth. The relationship between ICD and CWUA a ratio between ICD and CWUA was found. The overall mean ratio between ICD and CWUA was found to be 1.10. This indicates that the MDW of upper anterior teeth can be obtained by multiplying ICD with 1.10.